A pleiotropic QTL increased economic water use efficiency in bread wheat (Triticum aestivum L.) - Hui, Jian; Bai, Haibo; Lyu, Xuelian; Ma, Sishuang; Chen, Xiaojun; Li, Shuhua (Frontiers in Plant Science, 2023)
Wheat is one of the most important food crops in the world and drought can severely impact on wheat productivity. The identification and deployment of genes for improved water use efficiency can help alleviate yield loss under water limitation. In this study, a high-density genetic linkage map of wheat recombinant inbred lines (Ningchun 4 x Ningchun 27) containing 8751 SLAF tags (including 14757 SNPs), with a total map distance of 1685 cM and an average inter-marker map distance of 0.19 cM was constructed by SLAF SEQ technology. The economic yield WUE and nine related traits under three water treatments was monitored over four years. The results showed that loci conditioning WUE were also associated with grain carbon isotope discrimination (CID), Flag Leaf Chlorophyll content, plant height, 1000-grain weight, grain weight per spike and grain number per spike. One locus on chr 2B explained 26.3% WUE variation in multiple environments. Under good soil moisture conditions before flowering, the high CID genotype qWUE-2BNingchun 27, was associated with WUE, high panicle grain weight, and 1000 grain weight. Under rain-fed conditions, the low CID genotype qWUE-2BNingchun 4 tended to maintain more spike number and was associated with improved WUE and yield. In the future, the introduction of good chromosome fragments of qWUE-2B into elite lines by molecular marker assisted selection will help to speed up the cultivation of high-yield and water-saving wheat varieties.